Prostate-specific antigen mRNA and protein levels in laser microdissected cells of human prostate measured by real-time reverse transcriptase–quantitative polymerase chain reaction and immuno–quantitative polymerase chain reaction - Pinzani, Pamela; Lind, Kristina; Malentacchi, Francesca; Nesi, Gabriella; Salvianti, Francesca; Villari, Donata; Kubista, Mikael; Pazzagli, Mario; Orlando, Claudio (Human pathology, 2008)
Laser-assisted microdissection has mainly been used in cancer studies to excise pure cell populations from heterogeneous tissues. Cancer and normal cells selected by laser-assisted microdissection have frequently been used for mRNA expression studies usually by reverse transcriptase–quantitative polymerase chain reaction (qPCR). Recently, real time immuno-qPCR was developed as a new tool for highly sensitive measurements of proteins. Using reverse transcriptase–qPCR and immuno-qPCR, we measured the amounts of prostate-specific antigen mRNA and its corresponding protein in homogeneous and comparable cell populations, collected from normal and cancer prostates by laser-assisted microdissection. With these techniques, prostate-specific antigen mRNA and protein were quantified over a wide range of concentrations with a sensitivity sufficient to analyze single prostate cells (LNCaP). We did not find significant differences in prostate-specific antigen protein and mRNA between normal and cancer cells. The expression of prostate-specific antigen protein and mRNA was highly correlated in both normal and pathological cells. In microdissected peritubular stromal areas of prostate cancers, the concentration of prostate-specific antigen protein was about 100 times higher than in normal prostate, indicating an increased transit of secreted prostate-specific antigen. In the same samples, prostate-specific antigen mRNA was not detectable. Our data demonstrate, for the first time, the feasibility of simultaneous application of reverse transcriptase–qPCR and immuno-qPCR in studies of homogeneous cell populations, collected by laser-assisted microdissection. The approach is expected to become a very powerful tool for expression studies in human cancers at both mRNA and protein levels.